Bibliometric Computational Mapping Analysis of Publications on Sustainability and Islamic Finance - Rumaisah Azizah Al Adawiyah; Aas Nurasyiah; Suci Aprilliani Utami; Rida Rosida (ITB AAS INDONESIA Surakarta, 2023)
This study assesses the discourses of sustainability in Islamic Finance industry using a bibliometric approach to computational mapping analysis. This study acquires the article data from Google Scholar database with utilizing Publish or Perish reference manager application. The terms and article abstracts are used in channel the search process by employing keywords of â€œSustainability, Islam and Financeâ€. The results display 998 articles that are considered as being relevant with the topic. Google scholar indexed articles are used for ten-year period, from 2012 - 2022. From the results of the search, topics related with sustainability in Islamic Finance can be classified into four terms which are Sustainability, Islam, Islamic Finance and Finance. The term sustainability has 222 links with a total strength of 3997 links. The term Islam, based on the result has 208 links with 2435 links of strength. While the term Islamic Finance comprises 176 links with a total of strength is 1117 links. Afterwards the term Finance encompasses 201 links with a total of link strengths around 1727 links. Based on the trends, from 2012-2022, the research regarding sustainability and Islamic Finance is increasing steadily with a slightly decrease in 2015 to 2016. In 2022 up to September, the number of studies concerning the area of sustainability and Islamic Finance accounts for 79. This study observes the number of studies and the areas covered regarding the theme. The implication of this research could be a starting point in exploring research in sustainability and in the context with Islamic Finance role on it.